PENGARUH STRATEGI PROMOSI TERHADAP PENINGKATAN PENJUALAN DI CV. JAYA PERKASA MOTOR RANCAEKEK KABUPATEN BANDUNG - Kasino Martowinangun; Devita Juniati Sri Lestari; Karyadi Karyadi (Jurnal Co Management, 2019)
This research aimed to determine the promotional strategy and sales increase at CV. Jaya Perkasa Motor Rancaekek Kabupaten Bandung. The method used in this research was quantitative method with descriptive verification approach, that is the research method used to describe the facts or circumstances at the time the research took place and to test the truth of the hypothesis then concluded. Analysis results shows that the determinant coefficient (R2 ) between variables X and variable Y is R2 = 0,469 meaning that the contribution of X to Y is 46,9% and the remaining 53,1% is influenced by other factors not examined in this research, so the level of the relationship between determination of promotional strategy and sales increase is said to be good enough. The suggestion for the company must carry out adjustment in promotional improvements that are set to get the expected benefits and the company must be able to be more creative and innovative in carrying out all promotional strategy.